Tourism Human Resources Supporting Sustainable Development Towards the Vision of Golden Indonesia 2045 - Wirdayanti, Agnes; Triono, Wahyu; Nofita Sari, Sussy (Indonesian Association for Public Administration (IAPA), 2024)
Sustainable development is the main focus in achieving the vision of Golden Indonesia 2045. One sector that has great potential in realizing this vision is tourism. Human Resources in the tourism sector are key in supporting sustainable development. This study aims to identify the role of tourism Human Resources in supporting sustainable development towards the vision of Golden Indonesia 2045. The method used is a literature study to collect information related to the concept of sustainable development, tourism, and the role of Human Resources. The results of the study indicate that tourism Human Resources not only play a role as workers, but also as agents of change that affect environmental, social, and economic sustainability. In addition, skilled, trained, and competent tourism Human Resources can improve the quality of tourism services, maintain environmental sustainability, and promote local culture. The conclusion of this study is the importance of investing in the development of sustainable tourism Human Resources as a strategy to achieve the vision of Golden Indonesia 2045. What can be recommended from this paper is that public policies are needed to support the development of Human Resources capacity, including training programs, higher education, and collaborative initiatives between the government, tourism industry, and local communities. Thus, tourism Human Resources can be the main driving force in achieving holistic and sustainable development in Indonesia.